Memory reconsolidation may be disrupted by a distractor stimulus presented during reactivation - Crestani, Ana Paula (Sci Rep, 2015)
Memories can be destabilized by the reexposure to the training context, and may reconsolidate into a modified engram. Reconsolidation relies on some particular molecular mechanisms involving LVGCCs and GluN2B-containing NMDARs. In this study we investigate the interference caused by the presence of a distractor - a brief, unanticipated stimulus that impair a fear memory expression - during the reactivation session, and tested the hypothesis that this disruptive effect relies on a reconsolidation process. Rats previously trained in the contextual fear conditioning (CFC) were reactivated in the presence or absence of a distractor stimulus. In the test, groups reactivated in the original context with distractor displayed a reduction of the freezing response lasting up to 20 days. To check for the involvement of destabilization / reconsolidation mechanisms, we studied the effect of systemic nimodipine (a L-VGCC blocker) or intra-CA1 ifenprodil (a selective GluN2B/NMDAR antagonist) infused right before the reactivation session. Both treatments were able to prevent the disruptive effect of distraction. Ifenprodil results also bolstered the case for hippocampus as the putative brain structure hosting this phenomenon. Our results provide some evidence in support of a behavioral, non-invasive procedure that was able to disrupt an aversive memory in a long-lasting way.